Anlotinib Versus Sunitinib as First‐Line Treatment for Metastatic Renal Cell Carcinoma: A Randomized Phase II Clinical Trial. (22nd March 2019) - Zhou, Ai‐Ping; Bai, Yuxian; Song, Yan; Luo, Hong; Ren, Xiu‐Bao; Wang, Xiuwen; Shi, Benkang; Fu, Cheng; Cheng, Ying; Liu, Jiyan; Qin, Shukui; Li, Jun; et al.
Abstract: Background: Anlotinib is a tyrosine kinase inhibitor inhibiting angiogenesis. This multicenter, randomized phase II trial aimed to investigate the efficacy and safety of anlotinib in comparison with sunitinib as first‐line treatment for patients with metastatic renal cell carcinoma (mRCC). Materials and Methods: Patients with mRCC from 13 clinical centers were randomly assigned in a 2:1 ratio to receive anlotinib ( n = 90) or sunitinib ( n = 43). Anlotinib was given orally at a dose of 12 mg once daily (2 weeks on/1 week off), and sunitinib was given orally at 50 mg once daily (4 weeks on/2 weeks off). The primary endpoint was progression‐free survival (PFS). Secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), and safety. Results: The median PFS was similar with anlotinib and sunitinib (17.5 vs. 16.6 months, p > .05). The median OS (30.9 vs. 30.5 months, p > .05), ORR (30.3% vs. 27.9%), and 6‐week DCR (97.8% vs. 93.0%) were similar in the two groups. Adverse events (AEs) of grade 3 or 4 were significantly less frequent with anlotinib than with sunitinib (28.9% vs. 55.8%, p < .01), especially in terms of thrombocytopenia and neutropenia. AEs occurring at a lower frequency with anlotinib were hand‐foot syndrome, eyelid edema, hair depigmentation, skin yellowing, neutropenia, thrombocytopenia, and anemia. The incidence of serious AEs was lower with anlotinib than with sunitinib. Conclusion: The clinical efficacy of anlotinib was similar to that of sunitinib as the first‐line treatment for mRCC, but with a more favorable safety profile. Abstract : Renal cell carcinoma is the most common form of kidney cancer, and most cases are of the clear‐cell histologic subtype. This article reports on the efficacy and safety of anlotinib compared with sunitinib as first‐line treatment for patients with metastatic renal cell carcinoma with clear‐cell histology.